0
$\begingroup$

I have this function:

F[z_, y_, θ_] = Sqrt[3]/(2*π)*w^2/z^2 * 
 Exp[-w^2*(θ^2/z - 3*y*θ/z^2 + 3*y^2/z^3)]

I want to calculate

FT[ψ, θ5] = 
 Simplify[
   z3*F[z3, y3 - θ1*z3, θ3 - θ1] *
    F[z5 - z3, y5 - θ3*(z5 - z3) - y3, θ5 - θ3] *
    1 / (Sqrt[2 π] Subscript[σ, b]) *
    Exp[-(α + θ1)/(2*Subscript[σ, b]^2)], 
   TransformationFunctions -> {
     c = (a + b)/2, 
     θ13 = 2*z3/w^2, θ35 = 2*(z5 - z3)/w^2
   }
  ]

using TransformationFunctions to redifine the output. It is not clear to me why TransformationFunctions is not applied to the output. Could anyone help me ?

Thank you

Andrea

$\endgroup$
  • 1
    $\begingroup$ Welcome to Mathematica SE! You can solve θ13 == 2*z3/w^2, θ35 == 2*(z5 - z3)/w^2 for z3 and z5, then substitute these in your long expression and simplify. $\endgroup$ – Alx Sep 1 at 0:33
  • 1
    $\begingroup$ TransformationFunctions must be functions. You are giving expressions that should be supplied as Assumptions. (But use == not =) $\endgroup$ – mikado Sep 1 at 7:24
  • 1
    $\begingroup$ Unfortunately, Simplify[..., Assumptions->{θ13 == 2*z3/w^2, θ35 == 2*(z5 - z3)/w^2}] has no effect, that is the reason I suggested to use substitution. $\endgroup$ – Alx Sep 1 at 13:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.